Growth Hormone Secretagogue (A233) Improves Growth and Changes the Tissue Fatty Acid Profile in Juvenile Tilapia (Oreochromis niloticus). Issue 4 (14th April 2018) - Martínez, Rebeca; Morales, Carmen; Arenal, Amilcar; Morales, Antonio; Herrera, Fidel; González, Víctor; Estrada, Mario Pablo
Abstract: Growth hormone (GH) release is a process that is well regulated by several factors, including GH secretagogues. GH can mediate the regulation of the fatty acid level and composition. The aim of this study was to determine the effect of a synthetic GH secretagogue peptide (A233) on the growth and fatty acid composition in tilapia ( Oreochromis niloticus ). To address this objective, we administrated a diet supplemented with A233 to juvenile tilapia for 60 days. The group fed with a diet supplemented with 600 μg of A233 per kg of feed increased in weight (4.81 ± 0.09 g) and specific growth rate (2.49 ± 0.03%/day) compared to the control diet group (3.63 ± 0.08 g, 2.07 ± 0.04%/day; respectively) ( p < 0.001). In the muscle, the total lipids for the control diet group were higher than that in the group fed with 600 μg of A233 per kg feed; however, no differences were detected in the liver. In both tissues, the patterns of fatty acid composition and content were generally similar, with some exceptions. Tilapia fed with 600 μg of A233 per kg of feed showed, in liver and muscle, a significantly higher composition and content of n‐3 polyunsaturated fatty acids (such as 20:5n‐3, 22:5n‐3, 22:6n‐3) and n‐3/n‐6 PUFA than animals fed with the control diet. To our knowledge, this is the first report on the the effects of natural or synthetic GH secretagogues (GHS) on fatty acid composition, implying an increase in the nutritional quality of the tilapia.